Traditionally made brickwork (Bulletin KNOB, 2006)
In the middle ages and the subsequent period a range of possibilities existed to give brickwork a special finishing. This was also possible because the 'finishing phase' took considerably longer than became customary more recently through the application of Portland cement. It is remarkable that certain miniscule effects in relation to the surface of medieval brickwork occurred in North and South Europe simultaneously; people knew what was going on in the world, despite the fact that the production of brick was a local affair.In working with brick clamps a direct relation between bricklayer and brickmaker is obvious. Nevertheless this co-operation for special brickwork must have continued up to and including the 18th century, when the brick kilns supplied the bricklayers with various special-dimension bricks. Gauged brickwork, such as that of the masterpieces, reflects the highest ideal of perfectly and precisely executed masonry, which is a smooth and even wall surface, mathematically precise, built in Tudor bond or English bond with the pointing as narrow as possible. This ideal is to be seen in the perfectly built facades of monuments as they were built until the early 19th century.This tradition came to an end by the abolition of the guilds in 1808, which had set the requirement of producing a masterpiece. In the first half of the 19th century, however, carefully executed, 'ordinary' fair-faced brickwork continued to be made. The abolition of the guilds was accompanied by new, more theoretical forms of education during the 19th century.A final break with the past took place with the arrival the machine-manufactured moulded bricks, and particularly with the application of Portland cement, which entailed a completely new way of bricklaying with wider joints. On the one hand in the 20th century a contemporary conception of traditionally made brickwork developed, on the other hand historical pointing during 'restorations' was destroyed on a large scale. The so-called cut pointing is usually applied to camouflage too widely cut joints or brickwork with irregular bricks. It is a 20th-century restoration practice that has little to do with the historical starting point and is therefore undesired in the conservation of monuments and historic buildings.